Radiographic findings associated with postsurgical nerve alteration in lower third molar surgery - Pilco Guilcapi, Alexander Wladimir (2024)
Objective: To identify the radiographic findings associated with postsurgical nerve alteration in lower third molar surgery in patients treated in the Faculty of Odontology operating room from 2015 to 2019. Materials and methods: This cross-sectional study included a population composed of medical records and panoramic radiographs of patients who underwent lower third molar extraction at the Faculty of Odontology, Universidad Central del Ecuador (FOUCE), from 2015 to 2019. The sample was selected based on inclusion and exclusion criteria. Radiographic predictor signs were observed, and the presence or absence of nerve alteration was assessed from the evolution notes. Data were recorded in an Excel file, and statistical analysis was conducted using SPSS version 25.0. Descriptive statistics for absolute and relative frequencies, as well as the relationship between variables, were analyzed using the Chi-square test with a confidence level of 95%. Results: The frequency of nerve alteration was 3.8% (n = 16); for patients older than 25 years, it was 9.7% (n = 7). For the Pell and Gregory classification, type C and class II had frequencies of 4.4% (n = 6) and 2.4% (n = 13), respectively. The dark and bifid root sign was found in 8.7% (n = 2) of the cases with nerve alteration. Conclusions: In third molar surgery, radiographic signs such as dark and bifid roots, loss of the white line, and canal deviation are associated with postsurgical nerve alteration.